Synergistic UV protection effects of the lignin nanodiamond complex. (December 2021) - Yew, P.Y.M.; Zhu, D.D.; Lin, Q.Y.; Jiang, L.; Chee, P.L.; Leong, H.S.; Dong, Z.; Guo, X.D.; Kai, D.; Loh, X.J.
Abstract: There are various concerns with current sunscreen actives in the sun care industry which pushes for a natural-based active that is sustainable as well as effective. Lignin is a natural polymer, capable of ultraviolet (UV) filtration and maintaining photostability. In this study, a variety of tuneable lignin-poly(ethylene glycol) (LP) nanodiamond (LP–ND) complexes were developed with varying ratios of LP to NDs. There are two fractions of LP–NDs, which use detonation NDs (LP–rNDs) and furnace NDs (LP–mNDs). Both complexes demonstrated favorable UV filtration, enhanced photostability, and uniform dispersion in water and cream. The LP–mND had maintained its particle size at <200 nm with an increasing LP ratio from 0.5 to 20 times as opposed to the increased particle size of the LP–rND. The LP–mND complex excelled in its photostability during solar radiation from 1 h to 6 h, demonstrating its effectiveness in absorbing 70% in the UV B region. Results had indicated enhanced synergistic effect of LP–rNDs and LP–mNDs with commercial sunscreen. The LP–rND complex had enhanced the sunscreen from 29 to 62, whereas the LP–mND had further boosted the sun protection factor to 89. In a nutshell, the lignin nanodiamond complexes offer a sustainable alternative to current actives in the industry. Graphical abstract: In this study, we developed lignin-nanodiamond complexes as an effective broad-spectrum UV-filtering active that exhibits favorable photostability and antioxidative properties. Image 1 Highlights: The synergistic relationship of lignin and nanodiamonds demonstrates good UV-blocking capabilites as a suncsreen active. The performance of LP-r/mND complexes excels in both photostability and UV defense. Effective enhancements with commercially available sunscreens. The complexes effectively boost the SPF values of commerically available sunscreens.